2019
DOI: 10.20473/mog.v1i12019.28-33
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sitting and soaking therapy with binahong leaf (Anredera cordifolia) decoction on perineal wound healing

Abstract: Objective: To analyze the effect of sitting and soaking therapy with the decoction of Anredera cordifolia on the perineal wound healing in postpartum period mothers.Materials and Methods: The research method used is the Quasi-Experiment with pretest-posttest control group design, a sample of 62 primiparous postpartum period mothers with 2nd-grade perineal rupture. The sampling technique used is purposive sampling to obtain 31 respondents treated by 31 respondents. The wound healing variable was observed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Analysis of effect data using Anredera cordifolia decoction 25% containing perineal wound healing showed the effect of sitting and soaked Anredera cordifolia decoction on perineal wound healing for postpartum mothers. 27 Results of the ANOVA test indicated that these differences were significant (p=0.000). The ethanolic extract of binahong leaves was effective in wound healing.…”
Section: Discussionmentioning
confidence: 93%
“…Analysis of effect data using Anredera cordifolia decoction 25% containing perineal wound healing showed the effect of sitting and soaked Anredera cordifolia decoction on perineal wound healing for postpartum mothers. 27 Results of the ANOVA test indicated that these differences were significant (p=0.000). The ethanolic extract of binahong leaves was effective in wound healing.…”
Section: Discussionmentioning
confidence: 93%
“…Kandungan asam askorbat pada tanaman ini penting untuk mengaktifkan enzim prolil hodroksilasi yang menunjang tahap hidroksilasi dalam pembentukan kolagen sehingga dapat mempercepat proses penyembuhan luka. 8 Selain daun binahong daun sirih juga tergolong tanaman yang mempunyai banyak efek terapi. Daun sirih diketahui memiliki kandungan kimia yang berkhasiat sebagai obat antiseptik dan antibakteri selain itu daun sirih juga mengandung bahan kimia sebagai bahan anti inflamasi yang baik digunakan untuk membantu mempercepat proses penyembuhan luka.…”
Section: Pendahuluanunclassified